ANALISIS FAKTOR PENYEBAB KECELAKAAN KERJA DIPT. HANGLEKIU PLASTIK ABADI DENGANMENGGUNAKAN METODE HIRA DAN FTA SERTAIMPLEMENTASI TEOREMA BAYES PADA PERHITUNGANPROBABILITAS PERULANGAN KEJADIAN KECELAKAANKERJA - Rafi Dwizulfa (2023)
PT. Hanglekiu Plastik Abadi is an MSME that was established in 2021 and is engaged in the plastic cup chopping industry sector. After observing the SMEs, it can be seen that the workers who do the work are still not aware of the importance of occupational health and safety. It can be proven from the work accident report of PT. Hanglekiu Plastik Abadi had 8 work accidents with a frequency of 38 work accidents in a period of 4 months. This is detrimental to the company because the existence of work accidents can disrupt the flow of the production process. Researchers identified and measured risks related to work accidents using the HIRA method. From the HIRA method, the highest Risk Rating is High in workplace accidents with less ergonomic workplace factors and less ergonomic work positions. From the results obtained from HIRA, work accident factors are explained using the FTA to determine the countermeasures. From the results of the FTA, the calculation of Bayes' theorem was carried out and the percentage decreased by 42.4% for work accidents caused by falls that were not ergonomic and for falls caused by positions that were less ergonomic by 92.4%